Reading fiction and the development of literary competence in Slovene language classes in the digital age - Žbogar, Alenka (Slavia Centralis, 2025)
This article, examines how reading fiction within learning literature in Slovene language classes in the digital age is realized as a dialogic process, organized in stages, that contributes to the holistic development of literary competence. Parallels between literacy and literary competence and reading (fiction) are explored in terms of their effects, the medium (print vs. on-screen texts), and pupils’ developmental characteristics. Results from the international literacy studies PIRLS and PISA are examined, finding that literary competence is not measured in the latter. Influences of the digital environment on attention, reading motivation, and reading strategies are delved into, leading to the conclusion that the digital age requires a reconsideration of didactics of Slovene language and literature.